Efficacy and safety of intravenous belimumab in Japanese patients with systemic lupus erythematosus: A subgroup analysis of a phase 3 randomized placebo-controlled trial. Issue 3 (4th May 2019) - Tanaka, Yoshiya; Bass, Damon; Chu, Myron; Egginton, Sally; Ji, Beulah; Struemper, Herbert; Roth, David
Abstract: Objectives: To assess the efficacy and safety of intravenous (IV) belimumab plus standard systemic lupus erythematosus (SLE) therapy standard of care (SoC) in Japanese patients with SLE. Methods: A Phase 3, multicenter, double-blind, placebo-controlled, 52-week study (BEL 113750; NCT01345253) in patients with SLE, randomized 2:1 to belimumab 10 mg/kg plus SoC or placebo plus SoC to Week 48. Results: Sixty of 707 randomized patients were enrolled from study centers in Japan (belimumab, n = 39; placebo, n = 21). In this cohort, more patients achieved SLE Responder Index 4 response at Week 52 in the belimumab group compared with placebo (46.2% [18/39] vs. 25.0% [5/20]; odds ratio, 2.57 [95% confidence interval: 0.78, 8.47]; p =.1204). Fewer patients receiving belimumab experienced a severe flare through Week 52, with longer median time to flare compared with placebo. More patients with baseline prednisone dose >7.5 mg/d receiving belimumab had a dose reduction of ≥25% from baseline to ≤7.5 mg/d during Weeks 40–52, compared with placebo. No new safety issues were identified within the Japanese cohort. Conclusion: In Japanese patients with SLE, belimumab improved disease activity, with efficacy and safety results similar and consistent to the pivotal Phase 3 trials, suggesting that belimumab is a potential treatment option in this population.